2021
DOI: 10.1126/scirobotics.abh1221
|View full text |Cite
|
Sign up to set email alerts
|

Time-optimal planning for quadrotor waypoint flight

Abstract: Quadrotors are among the most agile flying robots. However, planning time-optimal trajectories at the actuation limit through multiple waypoints remains an open problem. This is crucial for applications such as inspection, delivery, search and rescue, and drone racing. Early works used polynomial trajectory formulations, which do not exploit the full actuator potential because of their inherent smoothness. Recent works resorted to numerical optimization but require waypoints to be allocated as costs or constra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
173
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(177 citation statements)
references
References 38 publications
4
173
0
Order By: Relevance
“…In maneuver or maneuver primitives, a drone is required to complete a certain position and attitude change in the shortest time; inspired by [24,[31][32][33][34][35], we formulated this problem as a keyframe-based time optimization problem. A schematic diagram of the problem is shown in Figure 5.…”
Section: Maneuver Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In maneuver or maneuver primitives, a drone is required to complete a certain position and attitude change in the shortest time; inspired by [24,[31][32][33][34][35], we formulated this problem as a keyframe-based time optimization problem. A schematic diagram of the problem is shown in Figure 5.…”
Section: Maneuver Optimizationmentioning
confidence: 99%
“…[33] emphasizes the Bang-Bang characteristics of the minimum time trajectory and compares the existing timeoptimal approaches, and through analysis, it is concluded that the polynomial method can only obtain non-optimal trajectories. On this basis, Foehn proposes complementary constraints [34] and solved both the time allocation and time-optimal trajectory planning problem elaborately. Through comparison and verification, it can be concluded that the trajectory designed by the algorithm is faster than that of professional pilots.…”
Section: Introductionmentioning
confidence: 99%
“…The recent work by Foehn et al [13] proposes a timeoptimal trajectory planning for a quadrotor flying through a sequence of points. A minimum time trajectory is computed given the maximum propulsion of each motor.…”
Section: Trajectory Planningmentioning
confidence: 99%
“…The nine first elements of the function f (x, u, Δt) are based on the movement of a rigid body. The bias states do not change on the propagation, only on the correction; thus, we have that f (x, u, Δt) is given by the vector: (13) in which J r ≡ J r φ, θ is the Jacobian matrix that transforms the angular velocities u ω in the derivatives of the Euler angles r. Note that the measurements u ω and u a are corrected with the bias states of the IMU. It is important to emphasize that the term u ω × vb is the Coriolis compensation and ẑ = [0, 0, 1] T .…”
Section: State Estimationmentioning
confidence: 99%
“…The two leading approaches are model-based and learning-based system design. The model-based approach follows a classical sense-plan-control scheme, which is modular, and requires very accurate knowledge about the drone dynamics, the drone’s state, and the ability to perform low-latency minimum-time control onboard [ 8 , 12 , 15 ]. Indeed, this approach has been very successful and has been able to outperform experienced drone racing pilots on challenging race maneuvers in highly controlled environments [ 8 ].…”
Section: Introductionmentioning
confidence: 99%